Effect Of Service Quality On Consumer Satisfaction Moderated By Government Policy During The Covid 19 Pandemic - Khair, Hazmanan; Tirtayasa, Satria; Eva Trisna, Fadila (International Journal of Science, Technology & Management, 2022)
The purpose of this study was to determine and analyze the effect of Service Quality on consumer satisfaction moderated by government policies during the covid 19 pandemic. The method used in this study is to use the explanatory approach. The population in this study were students in the city of Medan. The number of samples used in this study amounted to 140 people. Data collection techniques used in this study using a questionnaire technique/questionnaire. Data analysis techniques in this study using descriptive statistical analysis and data analysis with partial least square (PLS). Data processing in this study using Smart PLS 3 Software program. The results of this study showed that Tangibels has a positive and insignificant influence on consumer satisfaction, Assurance has a positive and significant influence on consumer satisfaction, Responsiveness has a positive and significant influence on consumer satisfaction, Empathy has a positive and significant influence on consumer satisfaction, Reability has a positive and significant influence on consumer satisfaction, Tangibels has a positive and insignificant influence on, Assurance has positive and insignificant influence on consumer satisfaction moderated by government policy, Responsiveness has positive and insignificant influence on consumer satisfaction moderated by government policy, Empathy has positive and insignificant influence on consumer satisfaction moderated by government policy, Reability has positive and insignificant influence on consumer satisfaction moderated by government policy.